Social determinants of health and health inequities in breast cancer screening: a scoping review - Jhumkhawala, Vama; Lobaina, Diana; Okwaraji, Goodness; Zerrouki, Yasmine; Burgoa, Sara; Marciniak, Adeife; Densley, Sebastian; Rao, Meera; Diaz, Daniella; Knecht, Michelle; Sacca, Lea (Frontiers in Public Health, 2024)
This scoping review aims to highlight key social determinants of health associated with breast cancer screening behavior in U.S. women aged >= 40 years old, identify public and private databases with SDOH data at city, state, and national levels, and share lessons learned from U.S. based observational studies in addressing SDOH in underserved women influencing breast cancer screening behaviors. The Arksey and O'Malley (2005) York methodology was used as guidance for this review: (1) identifying research questions; (2) searching for relevant studies; (3) selecting studies relevant to the research questions; (4) charting the data; (5) collating, summarizing, and reporting results. The 72 included studies were published between 2013 and 2023. Among the various SDOH identified, those related to socioeconomic status (n=96) exhibited the highest frequency. The Health Care Access and Quality category was reported in the highest number of studies (n = 44; 61%), showing its statistical significance in relation to access to mammography. Insurance status was the most reported sub-categorical factor of Health Care Access and Quality. Results may inform future evidence-based interventions aiming to address the underlying factors contributing to low screening rates for breast cancer in the U.S.